Unveiling the experiences through feeling in undergoing spiritual hypnotherapy with Islamic approach (SPHIA) for female children victim of incest - Low, Sofiyyah Siew Ping; Hassan, Siti Aishah; Mohd Noah, Sidek; Krauss, Steven Eric; Zainudin, Zaida Nor (Human Resource Management Academic Research Society, 2018)
Spiritual hypnosis is one of the specific treatment techniques in hypnosis, with the additional spiritual component. Spiritual interpretation suggested during hypnotic trance, and the reframing of symptoms to emphasize their spiritual meaning. Reframing must be in accordance with the client’s belief system in order to be accepted and for a change to take place. The study objective is to explore on what the informants experienced through listening when they are experiencing the Islamic spiritual hypnotherapy approach. A qualitative study using phenomenological research design was used to unveil the experiences of feeling with six female children who had histories of incest using spiritual hypnotherapy with Islamic approach. The individual stories of hypnotherapy experiences were collected through in depth interviews. Ethical issues were addressed. Spiritual Hypnotherapy with Islamic Approach (SPHIA), few elements that inserted in the hypnotherapy scripts are Dua, Azan, Dhikr, Surah Recitation and Salat. The script’s content has been validated by Islamic authorities in Malaysia. In the findings, the informants experiencing calmness, serenity and gratefulness during the process of hypnotherapy. Integrating Islamic Spiritual elements in hypnotherapy can help individual who lost and need help.